1999
DOI: 10.1002/(sici)1097-4628(19990509)72:6<751::aid-app3>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Friction and wear characteristics of metal sulfides and graphite-filled PTFE composites under dry and oil-lubricated conditions

Abstract: Five kinds of polytetrafluoroethylene (PTFE)-based composites, pure PTFE, PTFE ϩ 30(v)% MoS 2 , PTFE ϩ 30(v)% PbS, PTFE ϩ 30(v)% CuS, and PTFE ϩ 30(v)% graphite (GR) composites, were first prepared. Then the friction and wear properties of these PTFE composites, sliding against GCr15-bearing steel under both dry and liquid paraffin-lubricated conditions, were studied by using an MHK-500 ring-on-block wear tester. Finally, the worn surfaces and the transfer films of the PTFE composites formed on the surface of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 12 publications
3
12
0
Order By: Relevance
“…However, PTFE has been excluded from many tribological applications due to its high wear rate (∼10 −4 mm 3 /Nm) under engineering sliding conditions (Gong,et al (5), (6); Blanchet and Kennedy (7). A variety of filler compositions, shapes, and sizes have been added to PTFE, resulting in wear reductions ranging from a few percent to up to five orders of magnitude (Gong,et al (5), (6); Blanchet and Kennedy (7); Sawyer, et al (8); Tanaka and Kawakami (9); Bahadur and Tabor (10); Zhang, et al (11); Li, et al (12), (13); Khedkar,et al (14); Chen, et al (15); Klaas,et al (16); Burris and Sawyer (17); Lai, et al…”
Section: Introductionsupporting
confidence: 71%
“…However, PTFE has been excluded from many tribological applications due to its high wear rate (∼10 −4 mm 3 /Nm) under engineering sliding conditions (Gong,et al (5), (6); Blanchet and Kennedy (7). A variety of filler compositions, shapes, and sizes have been added to PTFE, resulting in wear reductions ranging from a few percent to up to five orders of magnitude (Gong,et al (5), (6); Blanchet and Kennedy (7); Sawyer, et al (8); Tanaka and Kawakami (9); Bahadur and Tabor (10); Zhang, et al (11); Li, et al (12), (13); Khedkar,et al (14); Chen, et al (15); Klaas,et al (16); Burris and Sawyer (17); Lai, et al…”
Section: Introductionsupporting
confidence: 71%
“…This increases the contact area between the asperities and the pin surface, causing more dragging or lateral force during sliding wear resulting in higher COF . Similar increasing trend in coefficient of friction was found for the polyetheretherketone (PEEK)/CuO, PTFE/Al 2 O 3 , PTFE/graphite, which was attributed to the increased contribution to the deformation component of friction by the hard CuO particles acting as third body abrasion during sliding against the composites. Sometimes, coefficient of friction of the composites might decrease, if these hard particles help in smoothing the countersurface.…”
Section: Resultssupporting
confidence: 87%
“…One of the main results is that graphite can be used in polymer materials as friction-reducing phase to increase the wear resistance and to decrease the friction coefficient of the polymers [5][6][7]14]. In this study, a similar conclusion can be drawn, as shown in Fig.…”
Section: The Synergistic Effect Of Graphite and Mosmentioning
confidence: 99%
“…Gong et al [5] and Zhang et al [6] found that both graphite powder and MoS 2 powder have the effect on reducing the wear loss of PTFE material when they being added in PTFE. These researchers also discovered that graphite powder can effectively lower the friction coefficient of PTFE while MoS 2 powder cannot.…”
Section: Introductionmentioning
confidence: 99%